PENGARUH CITRA MEREK TERHADAP KEPUTUSAN KONSUMEN MEMBELI MOBIL DAIHATSU XENIA PADA PT. MAKASSAR RAYA MOTOR CABANG PALU - Syamdi, Inten Suweno (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2019)
The purpose of this research is to find out and analyze the influence of brand image on consumer?s who buy Daihatsu Xenia cars at PT Makassar Raya Motor Branch Palu. The variables of this study are brand image which consists of the advantages of brand association, brand association strength and brand association uniqueness. While the dependent variable of Consumer's decision. The type of this research is descriptive causal. The sampling technique used purposive sampling with a sample size of 60 people. The analytical tool used is multiple linear regression analysis. The results of this study indicate that the variable brand image which consists of the advantages of brand association, the strength of brand association and the uniqueness of brand association simultaneously have a significant effect on consumer's decisions to buy a car Daihatsu Xenia in PT Makassar Raya Branch Motor of Palu. From the test results partially found that the variable of brand image which consists of the advantages of brand association, the strength of brand association and the uniqueness of brand association significantly influence consumer's decisions.